Explaining the UK’s ‘high-risk’ approach to type 2 diabetes prevention: findings from a qualitative interview study with policy-makers in England - Trisha Greenhalgh; Chrysanthi Papoutsi; Eleanor Barry; Sara Shaw (BMJ Open)
Objectives When seeking to prevent type 2 diabetes, a balance must be struck between individual approaches (focusing on people’s behaviour ‘choices’) and population approaches (focusing on the environment in which those choices are made) to address the socioeconomic complexity of diabetes development. We sought to explore how this balance is negotiated in the accounts of policy-makers developing and enacting diabetes prevention policy.Methods Twelve semistructured interviews were undertaken with nine UK policy-makers between 2018–2021. We explored their perspectives on disease prevention strategies and what influenced policy decision-making. Interviews were transcribed and analysed thematically using NVIVO. We used Shiffman’s political priority framework to theorise why some diabetes prevention policy approaches gather political support while others do not.Results The distribution of power and funding among relevant actors, and the way they exerted their power determined the dominant approach in diabetes prevention policy. As a result of this distribution, policy-makers framed their accounts of diabetes prevention policies in terms of individual behaviour change, monitoring personal quantitative markers but with limited ability to effect population-level approaches. Such an approach aligns with the current prevailing neoliberal political context, which focuses on individual lifestyle choices to prevent disease rather than on infrastructure measures to improve the environments and contexts within which those choices are made.Conclusion Within new local and national policy structures, there is an opportunity for collaborative working among the National Health Service, local governments and public health teams to balance the focus on disease prevention, addressing upstream drivers of ill health as well as targeting individuals with the highest risk of diabetes.